Public Communication Management for Strengthening The Marketing of MSME Products in Makassar City - Sahruddin Malik; Abdul Sahid; Andi Amitya Resty Dwiyanti; Syarifa Aeni MR; Irmawati Irmawati (Universitas Medan Area, 2025)
This study investigates public communication governance and its role in supporting the marketing of Micro, Small, and Medium Enterprises (MSMEs) in Makassar City, focusing on multi-actor collaboration, participation dynamics, and communication effectiveness. Using a qualitative approach, data were collected through in-depth interviews with government officials, MSME actors, supporting communities, and associations. Findings show a shift toward a more collaborative and participatory communication model, where MSMEs, communities, and government actors co-create strategies from planning to evaluation. The use of diverse communication channels—from social media and websites to informal networks—has improved MSMEs’ access to promotional programs, training, and policy information. Responsive feedback mechanisms and active stakeholder participation strengthen program relevance and effectiveness. However, persistent challenges remain, including digital literacy gaps, infrastructure limitations, and preferences for conventional communication. These findings underscore the need for adaptive, inclusive, and multi-layered communication strategies tailored to the diverse characteristics of urban MSMEs. The study recommends strengthening digital literacy, institutionalizing cross-sector collaboration, and conducting regular evaluations to sustain public communication innovations. By highlighting the strategic role of local communication governance, this research contributes to Indonesia’s broader agenda of enhancing MSME competitiveness and advancing an inclusive digital economy.